Reflections : my life in the deaf and hearing worlds - Christiansen, John B. (Gallaudet University Press, 2010)
Former social sciences professor Christiansen writes of growing up hard of hearing, his decision to get a cochlear implant, and his perspective on the 2006 protest at Gallaudet University.